Determination of Student Learning Motivation: Analysis of Islamic Religious Education Teacher Creativity (Determinasi Motivasi Belajar Siswa: Analisis Kreativitas Guru Pendidikan Agama Islam) - Sufiani, Sufiani (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
This article aims to describe the determination of student learning motivation, an analysis of PAI teacher creativity at SMA Negeri 1 Maligano. The research was conducted qualitatively with a narrative approach, where data collection was carried out through observation, interviews and documentation. Data analysis is carried out from data collection, data reduction, data display and data verification. Checking the validity of the data is carried out through a triangulation process, extending observations and increasing persistence. The results of the research show that the forms of creativity carried out by Islamic Religious Education subject teachers are opening and closing learning skillfully, explaining learning material, using varied learning models and methods, using appropriate learning media, providing variations, providing reinforcement, and using self-involvement techniques. This research is expected to provide information to Islamic Religious Education subject teachers and other subject teachers about the creativity of Islamic Religious Education teachers.Keywords: Learning Motivation, Islamic Education Teacher Creativity